Career Development of Functional Positions, Simpli ication of Organizational Structure, And Equality of Administrative Positions Into Functional Positions: A Literature Review - Grace Beatrix; Hijrah Apriyansyah; Faroman - Syarief (Sekolah Tinggi Manajemen IPMI, 2022)
The number of civil servants in Indonesia is decreasing from year to year. the structure of civil servants is still a serious matter because of the ineffectiveness of the existing echelon levels. Several policies have been carried out to reduce echelon levels. Echelon level simplification policy becomes necessary. That is why echelon level simplification policies and equalization of administrative positions need to be implemented so that employee career paths are clearer. This article reviews the factors that influence the simplification of organizational structure and equalization of administrative positions as executors of career development in functional positions. This paper aims to build a hypothesis based on the literature review and empirical studies that can be used for future studies. The review concludes that the simplification of the organizational structure and the equalization of administrative positions affects the career development of functional positions.